Examples of the Use of the Scientific Approach in Mathematics Teaching and Learning to Help Indonesian Students to be Independent Learners - Fadjar Shadiq (SEAMEO Regional Centre for QITEP in Mathematics, 2019)
This is a theoretical paper focusses on Indonesian school system. The challenge for education in Indonesia according to the former Minister of Education and Culture of Indonesia, Anies Baswedan, was how to help Indonesian students to be independent learners and to have good characters (Kemdikbud, 2014). The 2013 Curriculum proposed Scientific Approach to be implemented in Indonesian mathematics classes. Scientific Approach consists of five steps: (1) observing, (2) questioning, (3) collecting data, (4) reasoning, and (5) communicating. This paper discusses how two approaches, namely Scientific Approach and the Japanese Problem-solving Approach (PSA), can help Indonesian students to improve their thinking, creativity, and innovation during mathematics teaching and learning in classroom. The paper will provide some practical examples of problem-solving using these two approaches.